A Model of System and Strategic Financial Analysis of the Crimean Health Resorts - Malyshenko, Vadim Anatolyevich (Economy of Regions, 2016)
The subject matter of the research is the system of strategically focused financial analysis regarding an assessment of the financial condition of the enterprise. The hypothesis of the study is to assume the possibility of developing the financial and strategic model of the comprehensive assessment of the financial condition taking into account the integrated impact of environmental factors (general for the most Crimean health resorts). The methodology of the work is based on the most general principles of system analysis. The basic method of the research is the matrix method as the most common one for the system analysis. The graphical and statistical methods are also used. The result of the work is the comprehensive method of financial analysis developed as a model based on the matrix relation between the original visual profile of the internal environment and the dynamic type of external environment. The difference of the visual model of financial state from the existing graphic methods consists in fixing of the new strategic types of financial state on the basis of financial stability in visually grouped areas of financial coefficients in theme groups (configurations-profiles) with certain combinations of the forms and sizes. The new analytical instrument of «frigate model» can be applied in all analytical activities of the health resorts departments related to the analytical assessment of financial state. The advantage of «frigate model» in comparison with a classical method of the forming of the types of financial condition is that the proposed model allows to allocate more differentiated types and in addition, to identify the stages of enterprise life cycle based on the relative indicators of the analysis of financial state (objects-coefficients), and not just on the financial management. Through this, the consistency of interaction between the financial analysis and management is achieved.